Вплив режиму випуску продуктів плавки на роботу доменної печі - Кузнецов, Максим; Крячко, Геннадій; Сігарьов, Євген (Physico-technological Institute of Metals and Alloys, 2023)
The mode output of cast iron from the blast furnace, along with other modes of process management, is of significant technological importance. In the first part of the presented work, an analysis of works aimed at improving the mode parameters of the outlet system of blast furnaces was performed. The purpose of the second part of the work is to evaluate in a first approximation impact of changing discharge mode on the condition coke nozzle in the furnace, more specifically on the distance between levels air nozzles and cast iron fly-wheels, as well as on the stability temperature cast iron at the outlet from the furnace. Based on the analysis of domestic and foreign experience, it is shown that progress in blast furnace production is associated with the following changes in the design, parameters, and operation output system of furnaces. First, the uniformity of the placement of cast iron flys around the circumference of the furnace increases, which improves the drainage capacity of the coke nozzle. Secondly, there is a tendency to decrease the angle inclination of the channel of cast-iron fly with an increase in the absolute and relative depth of the sump. Thirdly, there is a transition from a temporary change in the diameter of the drill and, accordingly, the channel of the fly to the algorithmization selection and constant correction of this diameter in accordance with the change in the properties of the melting products and the release mode. It is shown that maintaining the maximum possible distance from the zone of air nozzles to the “gas – slag” interface in the coke nozzle before opening the cast iron fly is achieved due to the convergence mass rates of accumulation and release of melts. Therefore, a rational release technology should not be considered to be one in which an increase in the duration release is achieved by reducing its mass rate, but one in which a long release is maintained with similar rates of accumulation and release of melting products. It is also shown that when the productivity of the furnace increases and the number of releases increases, the preservation of their duration and speed release eliminates additional disturbances of the blast furnace process and is accompanied by a decrease in fluctuations in the temperature of cast iron.